Mecánica de rocas aplicada a la minería - Gómez Ruíz, David; Navarro, Víctor M.; Dixon, J. D. (My University, 1978)
A borescope (also called a borehole periscope or a strastascope) is an optical instrument udsed for visual inspection of boreholes. Important subsurface geologic information can be readily obtained by a borescope examination of small-diameter short (less than 100 ft) boreholes. During the past few years, the bureus of mine has frequently surveyed boreholes for obtaining the geometry (that is, spaicing, orientation, and aperture) of fractures in underground mine.
Keywords: rocas; geológicas; determinación; fracturas; projects